Cosmo-Multiculturalism: Towards Cosmopolitan Solidarity - Miščević, Nenad (Od filozofije poučevanja do poučevanja filozofije: Festschrift Rudi Kotnik, 2025)
Cosmopolitanism and multiculturalism are the main routes of escape from nationalism-populism. They can be combined, since there is no deep conflict between the two; moreover, their combination is consistent and desirable. It would be the global homeland of various vernaculars rather than a land of unitary Esperanto. The paper proposes relatively simple heuristics for passing from the usual multicultural conception to a cosmopolitan one. It lists the generally accepted requirements of multicultural solidarity and sketches the main lines of a cosmopolitan extension of them. Since a function of cosmopolitan norms is precisely to promote multicultural interests, this conception is conceptually coherent and morally progressive; one might hope that it is also politically feasible. This yields simple requirements on the cosmopolitan institutional structure needed to accommodate cultural pluralism.